Breynia pseudorostrata (Phyllanthaceae), a new species from Yunnan, Southwest China - Yang, Feng; Li, Ping-Ping; Liu, Jin-Li; Wang, Qiu-Ping; Wang, Huan-Chong (Phytotaxa, 2022)
Breynia pseudorostrata Huan C. Wang & Feng Yang, a new species in Phyllanthaceae, is described and illustrated. The new species was found in central Yunnan Province, southwest China. It morphologically resembles B. rostrata, but clearly differs from the latter by its ovate to elliptic leaf blades with broadly rounded to acute apex, styles strict, broad and nearly connate at base, stigmas with 2 shallow and completely inflexed lobes, and apex of capsule subtruncate.